Psikoedukasi Pengetahuan Menanamkan Respek pada Anak untuk Guru TK X - Alifa Astari Hendriana; Eva Septiana (Fakultas Psikologi Universitas Tarumanagara, 2022)
Not all of “X” preschool teachers apply the habit of saying please, sorry, thank you (TOMAT) in their daily life including in the school environment. Other than that, “X” preschool teachers also found not having enough knowledge on how to instill the habit on students in school. Therefore, the purpose of this study is to know the effectivity of psychoeducation to increase teacher’s knowledge on how to instill utterance TOMAT in children aged 5-6 with the total of participant included in this study is seven teachers (n=7). Effectivity of psychoeducation can be known through comparing scores between before and after psychoeducation is given. Wilcoxon Signed Ranks Test is used as method to test effectivity where significant results (p<0,05) is found on both pre-test – post-test 1 and post-test 1 – post-test 2. This result indicating that psychoeducation used in this study is effective to increase teacher’s knowledge on how to instill utterance of TOMAT in children aged 5-6. The psychoeducation can still affecting teacher’s knowledge even after 3 weeks it ended. Limitation of this study is that some participants already have enough knowledge on the habit of saying TOMAT therefore even after psychoeducation is given, the increase in their knowledge score is not too much. This study implicates that the increase of teacher’s knowledge can be done through psychoeducation that is suitable with the need or the difficulty the teachers have.